2003
DOI: 10.1007/s00232-003-2038-4
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Expression of the Prostate-specific Antigen by Claudin-7

Abstract: Claudins are a family of proteins involved in forming tight junctions between cells. Here we describe two forms of claudin-7 (CLDN-7), a full-length form of CLDN-7 with 211 amino-acid residues and a C-terminal truncated form with 158 amino-acid residues. These two forms of CLDN-7 are able to regulate the expression of a tissue-specific protein, the prostate-specific antigen (PSA), in the LNCaP prostate cancer cell line. We also found that the expression of CLDN-7 is responsive to androgen stimulation in the LN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 30 publications
1
44
1
Order By: Relevance
“…CLDN7 was also identified by a data base search as a member of the CLDN family (34). Forced expression of the CLDN7 gene up-regulated the expression of the prostate-specific antigen gene in a prostate-specific antigen-positive prostate cell line, suggesting a role for CLDN7 in the regulation of the gene (36). CLDN10 was formally deposited in GenBank TM as oligodendrocyte-specific protein (OSP)-like protein (OSP-L) homologous to OSP, which was isolated as the product of a gene with high and specific expression in myelinating oligodendrocytes (37) and later found to be a member of the CLDN family (34), although only limited information was available.…”
Section: Discussionmentioning
confidence: 99%
“…CLDN7 was also identified by a data base search as a member of the CLDN family (34). Forced expression of the CLDN7 gene up-regulated the expression of the prostate-specific antigen gene in a prostate-specific antigen-positive prostate cell line, suggesting a role for CLDN7 in the regulation of the gene (36). CLDN10 was formally deposited in GenBank TM as oligodendrocyte-specific protein (OSP)-like protein (OSP-L) homologous to OSP, which was isolated as the product of a gene with high and specific expression in myelinating oligodendrocytes (37) and later found to be a member of the CLDN family (34), although only limited information was available.…”
Section: Discussionmentioning
confidence: 99%
“…31 Cldn7 is responsive to androgen stimulation in the LNCaP prostate cancer cell line and can regulate the expression of prostate-specific antigen. 32 Recently, it was reported that Cldn7 is unlike other claudins, has both structural and regulatory functions and may be related to cell differentiation. 32 Thus, our results together with the growing data about claudins strongly suggest that some members of this large protein family are involved in epithelial tumorigenesis and may have an early diagnostic and or prognostic clinical value.…”
Section: Discussionmentioning
confidence: 99%
“…Claudin-7 displays a peculiar expression profile in epithelial cells of several organs, largely outside the TJ area and along the basolateral membrane (18)(19)(20). Factors regulating claudin-7 expression are largely unknown, although it was shown to be under the control of androgens in the prostate (21). In addition, hypermethylation of the claudin-7 gene promoter was reported as being responsible for the down-regulation of this protein in a panel of breast cancer cell lines (22).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental modulation of its expression regulates the paracellular leakage of Cl À and Na + in kidney cells (23), and a potential role of claudin-7 in cell differentiation has been suggested in the prostate, where claudin-7 regulates prostate-specific antigen expression (21). More recently, claudin-7 up-regulation in esophageal carcinoma cells was shown to increase E-cadherin expression and adhesive properties, and to reduce their invasive potential (24).…”
Section: Introductionmentioning
confidence: 99%